Aplikasi Sistem Informasi Geografis untuk Kajian Perencanaan Rehabilitasi Hutan Mangrove di Kecamatan Punduh Pedada, Lampung - Mohammad Ashari Dwiputra; Adib Mustofa; Budhi Agung Prasetyo (Journal of Science and Applicative Technology, 2020)
Mangrove forests are one of the coastal ecosystems that are under pressure due to antrophogenic activities, including land conversions to fishponds or aquaculture. On the other hand, the needs for seafood products from these aquaculture activities tend to increase annually. These situations become paradoxes that are often encountered within aquaculture management in Indonesia. Punduh Pidada Subdistrict is one of the areas in Pesawaran Regency, Lampung, that severely suffered from mangrove forest conversion into fishponds. The purposes of this study were to identify the trends in mangrove cover changes over 30 years and to design a mangrove rehabilitation plan in Punduh Pidada Subdistrict. This study used a time-series data of Landsat satellite imagery over 30 years, from 1989 to 2019. The results showed a significant decrease in the mangrove cover areas over 30 years at 83.34 Ha with an average mangrove cover losses at 30.5%. Three zones that are suitable for mangrove rehabilitation plan was then choosen based on the levels of mangrove loss areas, namely first priority rehabilitation plan covering zone 1 (1.7 Ha) and zone 2 (1.5 ha) and the second priority rehabilitation plan covering zone 3 (7.5 Ha). With a planting distance of 1 x 2 meter, the total of seeds needed for the rehabilitation planning are 8,500 seeds for zone 1, 7,500 seeds for zone 2, and 27,500 seeds for zone 3.